Identification of heterotic hybrids and good combiner parents in leaf variants CGMS system in pigeonpea (Cajanus cajan L.) - Gadekar, M.S.; Nandanwar, R. S.; Meshram, M. P.; Patil, A.N.; Sapkal, D.R. (The Indian Journal of Genetics and Plant Breeding, 2016)
Hybrids involving four diversified A2 cytoplasm based male sterile (CMS) lines viz., oval leaf, sesamum leaf, obcordifoliate leaf and small leaf, were selected and crossed with twelve diverse fertility restorer lines of pigeon pea (Cajanus cajan) and these lines with hybrids were evaluated for the estimation of heterosis, GCA and SCA effects and variances in Lines xTester analysis. Among the four CMS lines obcordifoliate leaf CMS line and three restorers AKPR-178 (M), AKPR-364 and AKPR-192 were found good general combiners for yield and yield contributing traits. Hybrids viz., Obcordifoliate leaf × AKPR-178 (M), Obcordifoliate leaf × AKPR-344 and Obcordifoliate leaf × AKPR-210 exhibited highest significant economic heterosis and SCA effects over two checks PKV-TARA and AKT-8811. Obcordifoliate leaf was found best leaf type for hybrids.